2023
DOI: 10.1021/acsfoodscitech.3c00055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Binding Mechanism of Bioactive Coumarins with Ovalbumin: Further Investigation into the Inhibitory Effects toward Protein Fibrillation

Abstract: Two bioactive coumarin derivatives, 7-hydroxycoumarin (7-HC) and 4-methyl-7-hydroxycoumarin (4-Me-7-HC), were used to investigate the molecular interactions with the main food allergen from egg white, ovalbumin (OVA), along with their inhibitory effects on OVA aggregation. The mechanism of binding interaction was elucidated by multispectroscopic and computational methods. Circular dichroism (CD) and Fourier transform infrared (FT-IR) experiments confirmed the ligand-induced conformational changes of OVA. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
1
1
0
Order By: Relevance
“…However, the absorption intensity is lower in the presence of UMB and 4-MU compared to F-pepsin alone, indicating reduced aggregate formation. This suggests that coumarin derivatives effectively act as an antifibrillating agent, consistent with previous research on ovalbumin protein, where UMB and 4-MU also demonstrated antifibrillation potential …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, the absorption intensity is lower in the presence of UMB and 4-MU compared to F-pepsin alone, indicating reduced aggregate formation. This suggests that coumarin derivatives effectively act as an antifibrillating agent, consistent with previous research on ovalbumin protein, where UMB and 4-MU also demonstrated antifibrillation potential …”
Section: Resultssupporting
confidence: 91%
“…The Rule of Five (RO5) addresses the relationship between active compounds and specifies four basic pharmacokinetic parameters: molecular weight, log P (partition coefficient), the number of H-bond donors, and the number of H-bond acceptors . As previously reported by the BOILED-Egg analysis, it was observed that both ligands are situated within the yolk region, this suggests that UMB and 4-MU are likely to have the capacity to penetrate the brain . As indicated in Table S6, both ligands fell within the acceptable molecular weight range and their H-bond donor and H-bond acceptor were also within the specified range of less than 5 and 10 respectively.…”
Section: Resultsmentioning
confidence: 62%
“…Previous studies have reported comparable findings with coumarin derivatives as an antifibrillating agent when investigated alongside pepsin and OVA protein fibrils. 96,97 3.11. Utilizing Molecular Docking Analyses to Identify the Potential Binding Site.…”
Section: Capability Of Daphnetin As a Potentialmentioning
confidence: 99%